ABOUT MODELING OF PRESSURE-FREE PRESSURE FILTRATION OF WATER IN URBAN CONSTRUCTION - V. I. Sologaev (Вестник СибАДИ)
The methodology of modeling pressure-free pressure filtration of water in urban construction is considered. A feature of this process is the presence of a creeping boundary of the free surface of water in a fractured porous medium if real nonstationary flows are considered as a function of time. The simplest one-dimensional case of pressure-free pressure filtration of water is considered. The hypothesis of the theory of filtration is stated, which allows to bring it to a new level of ideas about the motion of water in fractured-porous media with pressure-free flow. In contrast to the traditional point of view, the pressure for non-stationary filtration on the free surface of the water surface leaving the waterproof roof remains for some time in a state of vacuum, that is, below atmospheric. The author’s method of spreadsheets is proposed as a modeling tool. The motion of the creeping boundary is suggested to be realized using a conditional programming operator. The directions of the further development of the proposed methodology are indicated.